CARACTERIZACIÓN DE LAS LESIONES ENCONTRADAS EN BOVINOS CON HEMATURIA VESICAL ENZOÓTICA EN LA ZONA DE OXAPAMPA, PASCO - Gonzáles E., Christian (2004)
An anatomo-histopathologic study of the urinary bladder, liver, kidney and spleen from 41 Zebu and crossbreed cattle with different lesions of a disease commonly named as “hematuria” or Machicura´s intoxication was carried out in the Oxapampa province (Pasco). A total of 173 animals were inspected and samples from 41 animals with pathological lesions in bladder were collected at the local slaughterhouse. It was found that urinary bladder lesions were multifocal in 85.4% (35/41) of the cases. Tissue samples were processed with Hematoxiline-Eosine stain (HE), Hale´s histochemical stain for acid mucopolysaccharide and Masson trichromic for fibrous connective tissue with collagen or muscular fibres. The most important microscopic lesions were proliferative polips (24/ 41); the circulatory processes as haemorrhage (28/41), vascular proliferation or “angioblastic nests” (19/41), and inflammatory processes as the non suppurative cystitis (29/41). Neoplasias were found in the 68.3% of the cases (28/41), where 41.7% had epithelial origen and 58.3% were of non epithelial type. The epithelial types were represented by the in situ carcinoma (11/41) and mucous papilloma (4/41), whereas the hemangiosarcoma (14/41), hemangioma (10/41) and mixosarcoma (6/41) were the most frequent non epithelial neoplasias. Single cases of racemous papilloma, squamous cell carcinoma, tubular carcinoma, rhabdomyosarcoma, leiomyosarcoma, hemangiopericytosarcoma, lymphoma, and a lymphoid metastasis were observed. It is concluded that the well known process of “hematuria” corresponded to Bovine Enzootic Hematuria.